Traffic Generation Scheduling for Performance Improvement in WLAN Based Drone Networks - Cho, Jun Woo; Kim, Jae Hyun (International Conference on ICT Convergence, 2022)
Drone networks apply to the military, public, forest monitoring, and infrastructure monitoring and utilize video and image messages with high capacity. Thus, drone networks utilize WLAN to transmit them. However, WLAN is a contention-based protocol that requires competition to access channels, which can degrade network performance. In this paper, we propose a traffic generation scheduling that enables the effectiveness of a non-contention method in a WLAN-based drone network. Our proposed method is that AP performs scheduling with a new frame structure containing dynamic slots and transmits scheduling information (message generation time for the application layer and channel band). The method performs better than the existing method regarding latency and packet collision.
Keywords: Collision probability; Delay; Drone network; Forest monitoring; Generation scheduling; Infrastructure monitoring; Performance; Public forests; Traffic generation; WLAN; collision probability; delay; Drone networks; scheduling; WLAN